Case report: Aortoesophageal fistula—an extremely rare but life-threatening cardiovascular cause of hematemesis - Wong, Alexis Ching; Chou, Yu-Mou; Goh, Zhong Ning Leonard; Chang, Kuang-Fu; Seak, Chen-June (Frontiers in Cardiovascular Medicine, 2023)
Aortoesophageal fistula (AEF) is an extremely rare cardiovascular etiology of hematemesis and upper gastrointestinal bleeding. As such, its recognition and diagnosis are challenging and may be delayed when such patients present to the emergency department (ED). Without timely surgical intervention, AEF is almost always fatal. Awareness of AEF as a possible diagnosis and consequently early identification of these patients presenting to the ED are therefore crucial in optimizing clinical outcomes. We report a 45-year-old male presenting to the ED with the classical triad of an AEF (Chiari's triad)—midthoracic pain or dysphagia, a sentinel episode of minor hematemesis, then massive hematemesis with risk of exsanguination. The case report highlights the importance of considering the differential diagnosis of AEF when evaluating patients presenting to the ED with hematemesis, especially if they have predisposing risk factors such as prior aortic or esophageal surgeries, aortic aneurysms, or thoracic malignancies. Patients suspected of having AEF should be prioritized for early computed tomography angiography to expedite diagnosis and treatment.